SOME SOCIO-ECONOMIC ASPECTS OF THE USE OF DATA CENTERS - Chanyshev, R. I. (Systems and Technologies, 2024)
The article analyses the problems associated with the development of information technologies – cloud computing and artificial intelligence systems, which resulted in the mass construction of data processing centres. Such construction has led to the emergence of a number of socio-economic and environmental problems, such as: the problem with the lack of electricity for data centres and the uneven distribution of its resources, the problem with the noise created by the cooling systems of data centres, the problem of exhaustion of water resources required for cooling data centres, etc. These problems, given their novelty, have not yet found a proper solution and have not been practically investigated in scientific papers. The analysis of publications related to this topic shows that the main focus of researchers is on the study of the impact of information and communication technologies on the socio-economic development of society and on the life, education and social interactions of people. Economic issues are considered in terms of the impact of data centre construction on local economies and the revenue generation by governments and local authorities from the construction and operation of data centres. At the same time, the social and economic problems arising from the operation of data centres are not considered enough because of their recent emergence. This article discusses the problems of organisation, design and construction of data centres, including legal issues, and the associated social, economic and environmental problems. If at the time of the emergence of cloud computing technologies (in fact, since 2012) data centres were located on sites outside major population centres and had no problems with power supply and heat dissipation from the equipment, then nowadays data centres are built within cities or in close proximity to population centres. In this case, there are significant problems with power supply and ecology, in some cases leading to redistribution of capacities in favour of data centres at the expense of infringement of interests of the population. In addition, the rejection of water cooling of data centres for environmental reasons and the switch to air cooling has created the problem of unbearable noise emitted by air-cooled data centre systems, which has led to increased social tension and mass protests by local residents. The problem is aggravated by the fact that, according to analysts, the total number of data centers in the near future may increase by 2.5 times, which will inevitably lead to a sharp increase in social tension, mass protests and undesirable economic consequences. This problem is particularly important due to its worldwide nature, since data centers are being built in all regions of the planet. It is noted that the existing difficulties and problems arise due to the fact that local authorities failed to assess the possible problems with the operation of data centres and issued permits for their construction in order to gain financial benefits for the economy of the region. This problem is of an urgent nature and requires measures, including legislative measures, which could resolve the contradiction between the need to build data centres (and additional power plants to supply them, including nuclear power plants) and the interests of people living in the immediate vicinity of the data centres. In addition, it is mandatory to take into account the impact of the consequences of such construction on the environment. There are also known cases of destruction of cultural and historical heritage during the construction and operation of data centres. An important point is the issue of security associated with the possible consequences of terrorist actions (cessation of the functioning of vital information systems, contamination of the territory with toxic and radioactive substances, shutdown of power supply to the population). The article emphasises the need to urgently develop a set of measures, including legal ones, to address and prevent socio-economic and environmental problems.